CYCLIC WEAKLY AMENABLE SEMIGROUP ALGEBRAS WHICH ARE NOT WEAKLY AMENABLE (Journal of Academic Research, 2023)
In this paper we shall construct some examples where the semigroup algebra  is cyclic weakly amenable but not weakly amenable ,where  is a commutative, 0-cancellative, -semigroup.
Keywords: semigroup algebra; cyclic weakly amenable